Thinking between cultures pragmatism, rorty and intercultural philosophy (2008)
The paper discusses Rorty's critique and special relation to intercultural thinking. It looks into the history of both pragmatism and intercultural philosophy, discusses some of their possible points of convergence, and finally follows the implications of this encounter for our intercultural understanding of Rorty's version of pragmatism, especially in the context of a contemporary North-South intercultural dialogue.